KOMPARASI KOMPETENSI IPA SISWA ANTARA MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE (TPS) DENGAN SNOWBALL THROWING PADA KELAS VII SMPN 11 PADANG - Yana Ramadhani; Akmam Akmam; Letmi Dwiridal (PILLAR OF PHYSICS EDUCATION, 2016)
One of the problems that makes the competence of the students are not aptimal is that we have not found can be the suitable learning model between Cooperative Learning type Think-Pair-Share and Snowball Throwing in order to increase student competence. The purpose of this research was to know the difference in competence of the IPA students used Cooperative Learning type Think-Pair-Share and Snowball Throwing for class VII SMPN 11 Padang. This research was Quasi experiment research with factorial design 2 x 2. The population research  was students in class VII SMPN 11 Padang that enrolled on second semester in academic year of 2015/2016. The instruments of this research are paper test for cognitive competence, observation sheets for affective competence, and performance assessment for psychomotor competence. Hypotesis test used was the t-test. Based on data analysis result, it can be concluded that in cognitive competence and psychomotor tcounting > ttable, it shows that Cooperative Learning type Snowball Throwing is better than Cooperative Learning type Think-Pair-Share, but psychomotor competence tcounting <ttable., there is no difference between usage Cooperative Learning type Think-Pair-Share and Snowball Throwing models at  SMPN 11 Padang